Influence of head-tip morphology on contact properties for microconnector of Ni–Co alloy - Bhuiyan, M. M. I.; Quadri, H. A.; Bhuiyan, Moinul; Kajihara, M. (Springer New York, 2013)
To examine experimentally the influence of head-tip morphology on electrical and mechanical properties at the contact with a phosphor bronze, cantilevertype microconnectors of Ni–Co alloys were prepared by an electroplating technique. Here, the mol fraction y of Co in the Ni–Co alloy is 0.178, 0.204, 0.233 and 0.299. Among these alloys, the Vickers hardness is HV = 510, 518, 525 and 478 for y = 0.178, 0.204, 0.233 and 0.299, respectively. Since the Vickers hardness is the maximum for y = 0.233, the Ni–0.233Co alloy may indicate the best wear-resistance. The loading and unloading manipulations were repeated to measure electrical resistance at the mechanical contact between the Ni–0.233Co microconnector and the phosphor bronze up to 103 times. The repetitive measurement was conducted for microconnectors with thickness of 45 lm and head-tip curvature radii of r = 5, 25, 50 and 200 lm. Even at the initial repetition, the reliable electrical contact is actualized for r = 5 lm but not for r = 25–200 lm. The experimental result was quantitatively analyzed using a mechanical model. The analysis provides that the impression depth z of the headtip into the phosphor bronze at the contact is mostly